Seismic retrofitting of RC joints using steel cage and haunch with bolted steel plate. (September 2022) - Deng, Bo-Yu; Liu, Xin; Yu, Ke-Quan; Li, Ling-Zhi; Chen, Yu
Abstract: Two novel combination retrofitting systems for RC joint have been proposed and investigated experimentally in this research. The beams and columns were strengthened by bolted steel plates, and the joint panel zones were strengthened by the steel cages or steel haunches. Based on cyclic loading tests, the seismic behaviours of retrofitted RC joints were studied compared with a non-retrofitting counterpart, in terms of failure mode, strength, ductility, stiffness degradation, hysteretic curve and energy dissipation. For the retrofitted joint with steel cage, the ultimate load capacity, initial stiffness and ductility factor were increased by a maximum proportion of 94 %, 75 % and 28 %, respectively. For the retrofitted joint with steel haunch, the ultimate load capacity and initial stiffness were significantly increased by 134 % and 239 %, while the ductility factor was decreased by 23 %. The shear deformation of core area, curvature of beam and strain of steel element are also evaluated. The proposed rehabilitations seismically upgrade the joint panel zone together with the adjacent members and thus enhance the joint performance comprehensively. The combination retrofitting of bolted steel plate and steel cage provided superior ductility and energy dissipation, while the combination of bolted steel plate and steel haunch caused the undesirable shear failure due to the shorter deformable length and insufficient shear strengthening of the beams. The efficiency and feasibility of the proposed combination retrofitting systems were validated and the recommendations for improvement are provided.